Sustainable Energy Delivery for Africa’s Changing Climate: An Economic Assessment - Quartey, Jonathan D. (Asian Development Policy Review, 2020)
This paper assesses Africa’s energy future in a changing global climate to inform development policy. In the midst of economic and energy challenges, coupled with COVID-19 pandemic recovery, Africa is expected to meet global climate obligations. While it makes sense to develop climate resilient economies, Africa appears stuck in its pre-climate change energy delivery systems. The economic, social and environmental consequences of this stagnation are suboptimal for the continent, calling for urgent transition to more sustainable energy delivery. The study analyzed fossil fuel use in Africa from 1960 to 2016, based on a modified Hotelling Rule. Through time series data, the sustainable marginal cost of energy for Africa was estimated. The study further derived the optimal point in time when Africa should switch from fossil fuels as a main source of electricity generation to renewable energy, due to climate change. The study finds more than 70 percent increase in the marginal cost of fossil fuel compared to a cumulative reduction of 80 percent in the marginal cost of solar photovoltaic over the study period. Also, the switch point to renewable energy as the main source of electricity in Africa was found to be 2003. For sustainable delivery of energy in Africa, the study recommends policies to internalize the externalities of fossil fuel, backed by recovery subsidies to make up for the loss of welfare from fossil fuel use, and to create an enabling environment for a speedy energy transition in Africa’s changing climate.